Two CES1 Gene Mutations Lead to Dysfunctional Carboxylesterase 1 Activity in Man: Clinical Significance and Molecular Basis - Zhu, Hao-Jie; Patrick, Kennerly S.; Yuan, Hong-Jie; Wang, Jun-Sheng; Donovan, Jennifer L.; DeVane, C. Lindsay; Malcolm, Robert; Johnson, Julie A.; Youngblood, Geri L.; Sweet, Douglas H.; Langaee, Taimour Y.; Markowitz, John S. (American journal of human genetics, 2008)
The human carboxylesterase 1 ( CES1) gene encodes for the enzyme carboxylesterase 1, a serine esterase governing both metabolic deactivation and activation of numerous therapeutic agents. During the course of a study of the pharmacokinetics of the methyl ester racemic psychostimulant methylphenidate, profoundly elevated methylphenidate plasma concentrations, unprecedented distortions in isomer disposition, and increases in hemodynamic measures were observed in a subject of European descent. These observations led to a focused study of the subject's CES1 gene. DNA sequencing detected two coding region single-nucleotide mutations located in exons 4 and 6. The mutation in exon 4 is located in codon 143 and leads to a nonconservative substitution, p.Gly143Glu. A deletion in exon 6 at codon 260 results in a frameshift mutation, p.Asp260fs, altering residues 260–299 before truncating at a premature stop codon. The minor allele frequency of p.Gly143Glu was determined to be 3.7%, 4.3%, 2.0%, and 0% in white, black, Hispanic, and Asian populations, respectively. Of 925 individual DNA samples examined, none carried the p.Asp260fs, indicating it is an extremely rare mutation. In vitro functional studies demonstrated the catalytic functions of both p.Gly143Glu and p.Asp260fs are substantially impaired, resulting in a complete loss of hydrolytic activity toward methylphenidate. When a more sensitive esterase substrate, p-nitrophenyl acetate was utilized, only 21.4% and 0.6% catalytic efficiency ( V max / K m ) were determined in p.Gly143Glu and p.Asp260fs, respectively, compared to the wild-type enzyme. These findings indicate that specific CES1 gene variants can lead to clinically significant alterations in pharmacokinetics and drug response of carboxylesterase 1 substrates.